Identification of Tumor Microenvironment-Related Prognostic Biomarkers in Luminal Breast Cancer - Wang, Yanyan; Zhu, Mingzhi; Guo, Feng; Song, Yi; Fan, Xunjie; Qin, Guijun (Frontiers in Genetics, 2020)
Background: The tumor microenvironment (TME) has been reported to have significant value in the diagnosis and prognosis of cancers. This study aimed to identify key biomarkers in the TME of luminal breast cancer (BC). Methods: We obtained immune scores (ISs) and stromal scores (SSs) for the TCGA luminal BC cohort from the online ESTIMATE portal. The relationships between ISs and SSs and the overall survival of luminal BC patients were assessed by the Kaplan-Meier method. The differentially expressed mRNAs (DEmRNAs) related to the ISs and SSs were subjected to functional enrichment analysis. Additionally, a ceRNA network was constructed with differentially expressed miRNAs (DEmiRNAs) and lncRNAs (DElncRNAs). Furthermore, a protein-protein interaction (PPI) network was established to analyze the DEmRNAs in the ceRNA network. Then, survival analysis of biomarkers involved in the ceRNA network was carried out to explore their prognostic value. Finally, these biomarkers were validated using the luminal BC dataset from the Gene Expression Omnibus (GEO) database. Results: The results showed that ISs were significantly associated with longer survival times of luminal BC patients. Functional enrichment analysis showed that the DEmRNAs were mainly associated with immune response, antigen binding and the extracellular region. In the PPI network, the top 10 DEmRNAs were identified as hub genes that affected on the TME of luminal BC. Finally, 2 DEmiRNAs, 2 DElncRNAs and 17 DEmRNAs of the ceRNA network associated with the TME were shown to have prognostic value. Subsequently, the expression of 15 prognostic biomarkers was validated in one additional dataset (GSE81002). In particular, one lncRNA (GVINP1) and 5 mRNAs (CCDC69, DOCK2, IKZF1, JCHAIN and NCKAP1L) were novel biomarkers. Conclusions: Our studies demonstrated that ISs were associated with the survival of luminal BC patients, and a set of novel biomarkers that might play a prognostic role in the TME of luminal BC was identified.